Analisis Kinerja Anggota Dewan Perwakilan Rakyat Daerah Kota Parepare - Sapri Sapri (PRAJA: Jurnal Ilmiah Pemerintahan, 2019)
Abstract This research was aimed to determine The Parliament’s supervising function effectivity on the performance of Pare-Pare City Local Government, along with all influencing factors. The study was a type of descriptive-qualitative. Data were collected by using observation, questionnaires, interviews, and documentation. Then those data were analyzed using frequency tables and percentages. The results showed that The Parliament’s supervising function effectivity on the performance of Pare-Pare City Local Government had not yet optimally achieved, meaning that Pare-Pare legislators had not yet a high sense of responsibility in carrying out their role and function, and the discipline level of board members, as well as an understanding of duties and authority, also the rights and obligations of Pare-Pare legislators. However, in majority the education level of Parliament Parepare was quite adequate at bachelor level, and also had a fairly young age. Basically there were two main influencing factors against the ability of Pare-Pare legislators in order to increase supervising function effectively. The internal factors concluded the human resources of board members, facilities and infrastructure availability, leaders’ policy, and each Pare-Pare legislators’ attitudes. While external factors concluded carrying capacity of other institutions, political parties, the electoral system through national election and community organizations such as NGOs and the press.